Himpunan Modul TMK Untuk Sekolah Siri 1 - Abu Ziden, Azidah; Abd Aziz, Mohd Ismail; Gunasegaran, Thenmolli; Abdullah, Nurhanim Saadah (Unit Penyelidikan Pendidikan Asas, USM, 2016)
Compilation of ICT Modules for Schools